2015
DOI: 10.1093/jamia/ocv097
|View full text |Cite
|
Sign up to set email alerts
|

Delivering digital health and well-being at scale: lessons learned during the implementation of the dallas program in the United Kingdom

Abstract: Objective To identify implementation lessons from the United Kingdom Delivering Assisted Living Lifestyles at Scale (dallas) program—a large-scale, national technology program that aims to deliver a broad range of digital services and products to the public to promote health and well-being.Materials and Methods Prospective, longitudinal qualitative research study investigating implementation processes. Qualitative data collected includes semi-structured e-Health Implementation Toolkit–led interviews at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 31 publications
3
72
0
Order By: Relevance
“…Barriers and opportunities exist that incorporate new technology for both providers and consumers. Since the locus of healthcare is shifting to the home and community setting, there is an increasing need to adopt a broader approach across the traditional boundaries of health and social care in order to operationalize a more integrated and personalized healthcare service provision [34].…”
Section: Mobile Technologymentioning
confidence: 99%
“…Barriers and opportunities exist that incorporate new technology for both providers and consumers. Since the locus of healthcare is shifting to the home and community setting, there is an increasing need to adopt a broader approach across the traditional boundaries of health and social care in order to operationalize a more integrated and personalized healthcare service provision [34].…”
Section: Mobile Technologymentioning
confidence: 99%
“…Previous research suggested that multi-disciplinary cooperation is essential for effective implementation of digital health. [25] We designed, developed, and evaluated the "Talking Pole" through an inter-disciplinary approach, so that we could see that multi-disciplinary cooperation has an advantage in the implementation of digital health. Participants of this study were patients and caregivers.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Furthermore, the proposed digital platforms earmarked for development as part of the program were intended to cross many organizational and cultural boundaries (health and social care for example) as well as being targeted at multiple geographies and populations [15][16][17][18]. From the outset our overall evaluation approach had three aspects as illustrated in Table 1 (descriptive, process and outcome) with a fixed underpinning theoretical framework, Normalization Process Theory (NPT) [19,20] to help us capture and organize the implementation data.…”
Section: Evaluation Frameworkmentioning
confidence: 99%
“…1 The dallas program funded four large multi-stakeholder consortia called 'Living It Up', 'Year Zero', 'More Independent', and 'i-Focus' [15][16][17][18]. These were jointly led by a variety of health and social care services, private industry, the voluntary sector, local government agencies and in some cases, supported by academic research partners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation